Effect of Admission Serum Calcium Levels and Length of Stay in Patients with Acute Pancreatitis: Data from the MIMIC-III Database - Dongyan Wang; Xiaoyan Guo; Wenwen Xia; Zhijuan Ru; Yihai Shi; Zhengyu Hu (Emergency Medicine International)
Objective. We retrospectively investigated the effect of admission serum calcium levels on length of stay (LOS) in patients hospitalized with acute pancreatitis (AP). Methods. Clinical data for 3156 patients diagnosed with AP were obtained from the Multiparametric Intelligent Monitoring in Intensive Care III (MIMIC-III) database. Restricted cubic spline curve (RCS) functions of dose-response analysis curves and logistic regression analysis were used to analyze the relationship between admission serum calcium levels and the LOS. Results. All patients were divided into 2 groups (<8.5 mg/dl group and ≥8.5 mg/dl group) based on RCS analysis. RCS showed a significant nonlinear negative correlation between blood calcium levels and the LOS (p<0.001). In addition, compared with patients with blood calcium <8.5 mg/dl, multivariate logistic regression analysis showed that patients with blood calcium ≥8.5 mg/dl had a reduced risk of the LOS >2 days (aOR = 0.653; 95% CI 0.507–0.842; p=0.001), a reduced risk of the LOS >5 days (aOR = 0.589; 95% CI 0.503–0.689; p<0.001), and a reduced risk of the LOS >7 days (aOR = 0.515; 95% CI 0.437–0.609; p<0.001). And similar results were found in the subgroup analysis. Conclusion. Our findings suggest that low blood calcium increases the LOS in patients with AP. More attention is needed for patients with combined low blood calcium levels (<8.5 mg/dl) in hospitalized AP patients.